2019
DOI: 10.3390/fermentation5010013
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Production and Quantitative Evaluation of Nigericin from the Algerian Soil-Living Streptomyces youssoufiensis SF10 Strain

Abstract: Nigericin, one of the main ionophoric polyethers produced by various Streptomyces strains, presents relevant biological activities including antibacterial and recently studied antitumor properties. This work describes the influence of different culture conditions on the production of this metabolite by Streptomyces sp. SF10, isolated from a semi-arid soil sample collected at Chélia Mountain, in Khenchela (Northeastern Algeria) and identified as Streptomyces youssoufiensis. The extracts from the strain, culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…The higher yield of crude antimicrobial extract obtained using the solid-state fermentation method was consistent with previous reports 59 – 63 . Surprisingly, one study showed that solid-state fermentation conditions are ideal for producing antimicrobial compounds by Streptomyces youssoufiensis SF10 strain 64 .…”
Section: Discussionmentioning
confidence: 99%
“…The higher yield of crude antimicrobial extract obtained using the solid-state fermentation method was consistent with previous reports 59 – 63 . Surprisingly, one study showed that solid-state fermentation conditions are ideal for producing antimicrobial compounds by Streptomyces youssoufiensis SF10 strain 64 .…”
Section: Discussionmentioning
confidence: 99%
“…By the co-culture with Streptomyces sp., the formation of phenylacetic acid was observed, a metabolite previously reported from S. humidus cultures showing inhibition on some plant-pathogenic fungi. Otherwise, co-culturing SF10 strain with S. coeruleorubidus neither nigericin nor phenylacetic acid were observed [106].…”
Section: Antimicrobialsmentioning
confidence: 91%
“…Glycerol inhibited cephamycin c and induced the formation of clavulanic acid by this strain (Saudagar and Singhal, 2007). Leulmi et al (2019) reported that, while D-glucose enhanced nigericin production by Streptomyces youssoufiensis SF10 strain, ribose or mannitol decreased nigericin production, but sucrose or starch inhibited nigericin production. In the present study, both glycerol and glucose stimulated the production of the antimicrobial agent(s), but maltose and starch suppressed the synthesis of the antimicrobial agent(s) by NMF76 strain when supplemented separately to the culture medium.…”
Section: Discussionmentioning
confidence: 93%